Successful Management of Cataract in Patient With Long Anterior Zonules and Small Pupil :A Rare Case: Poster Presentation - Case Report - Ophthalmologist - Pangestika, Riskha; Rhendy, Rio; Widyawati, Syska (Majalah Oftalmologi Indonesia, 2023)
Introduction : Long anterior zonules (LAZ) are rare disease with prevalence was 1–2%, characterized by zonular fibers that extend centrally leading to a small zonule-free zone (ZFZ), which raises the risk of complications during zonular cutting while continuous curvilinear capsulorhexis (CCC). This leads to two options whether to perform phacoemulsification through a small CCC within the small ZFZ or an adequately sized CCC. The objective of this study was to report challenging management of phacoemulsification surgery with LAZ eyes with small pupil Case Illustration : A 62 y.o female had visual acuity(VA) 0.7(logMAR) due to corticonuclear cataract in left eye. She had history complicated cataract surgery with secondary sulcus fixated IOL in her fellow eye. The IOP was normal, no phacodenesis and pseudoexfoliative material observed in left eye. The posterior segment was normal. The left eye observed otherwise normal in initial examination. Intraoperatively, after viscomidriasis technique the ZFZ identified in the area of 2.0-2.5 mm from central. Five millimeter CCC can be achieved in the central area and phacoemulsification with the help of CTR (Capsular Tension Ring) safely performed and one piece IOL was implanted in the bag. Discussion : On the first postoperative day, VA was improves to 0.4(logMAR), IOL central and clear corneal with minimal inflammation. One week after surgery, the VA 0.3(logMAR) and no sign of IOL decenteration. Conclusion : Phacoemulsification in eyes with LAZs can be safely performed with CTR through an adequately sized CCC without significant complications. A combination of early recognising high-risk eye, proficient skills, and surgical instruments can improve outcome.